Tolerogenic Dendritic Cells: The Pearl of Immunotherapy in Organ Transplantation - Zhuang, Quan; Cai, Haozheng; Cao, Qingtai; Li, Zixin; Liu, Shu; Ming, Yingzi (Frontiers in Immunology, 2020)
Over a half century, organ transplantation has become an effective method for the treatment of endstage visceral diseases. Although the application of immunosuppressants (IS) minimizes the rate of allograft rejection, the common use of IS brought many adverse effects to transplant patients. Moreover, true transplant tolerance is very rare in clinical practice. Dendritic cell (DC) is thought to be the most potential antigen presenting cell which makes a bridge between innate and adaptive immunity. Among their subsets, a small portion of DC with immunoregulatory function was known as tolerogenic DC (Tol-DC). Previous reports demonstrated the ability of adoptively transferred Tol-DC to approach to transplant tolerance in animal models. In this study, we summarized the properties, ex-vivo generation, metabolism and clinical attempts of Tol-DC. Tol-DC is expected to become a substitute for IS to enable patients to achieve immune tolerance in the future.